SCREENING OF FOUR FOOD SPICES OF PLANT ORIGIN FOR ANTIFUNGAL ACTIVITY AGAINST A FUSARIUM OXYSPORUM SOIL ISOLATE - Okungbowa Francisca Iziegbe (Jurnal Teknologi dan Industri Pangan, 2011)
Cold and hot water extracts of four food spices (Aframomum melegueta, Allium sativum, Zingiber officinale, and Monodora myristica) were studied for antifungal activity against a Fusarium oxysporum soil isolate. The study was necessitated by the current search for bioactive substances of plant origin in the bid to control disease-causing organisms. The Fusarium isolate was grown on Potato Dextrose Agar (PDA) and in Potato Dextrose Broth (PDB) containing 100, 50, 25 or 12.5% of each extract and incubated for 7 days (solid cultures) and 5 days (liquid cultures) at room temperature (28 ±2 oC). Mycelial radial growth was measured on the 7th day while dry weight of mycelium was determined after 5 days. Results showed that all tested spice plants had antifungal effect in the liquid cultures. Cold extracts were more effective as their percentage inhibition values were consistently, though insignificantly higher, than for hot extracts, except for A. sativum which had a significantly higher value (82.4% as against 55.5% for cold and hot extracts, respectively, at 100% concentration). Allium sativum had the highest inhibitory effect (82.4%) while M. myristica had the least (45.3%) for cold extracts in liquid cultures. For radial growth, Z. officinale, and M. myristica had no effect (cold extract) while M. myristica (hot extract) had no effect. These results indicate that the tested plants have antifungal potential that could be harnessed for the control of F. oxysporum. High temperatures seem to reduce the activity of the extracts. For future studies liquid cultures would be more effective.